Detection of Helicobacter pylori adhesion factor Baba from endoscopic tissue biopsy and bacterial isolates : clinical and histopathological relevance - Elhashim, Tariq Mohammad (Kulliyyah of Medicine, International Islamic University Malaysia, 2015)
H. pylori BabA is an outer membrane protein that mediates bacterial adherence to the gastric epithelium. Additionally, it triggers several pathways during the course of infection, and thus contributes to the disease development. Considering the variable presence of BabA coding gene among H. pylori clinical strains, the aim of this study was to assess the relationship between the status of H. pylori BabA and the severity of clinical and histopathological outcomes. Gastric mucosal biopsy specimens were collected from 30 CLO test-positive patients, 16 with gastritis and 14 with peptic ulcer disease. Polymerase chain reaction was carried out to detect the presence of BabA coding gene (babA2). Histopathological examination was performed to evaluate the severity of H. pylori-associated gastric disease according to the Updated Sydney Classification System. We found that babA2 gene was present in 86.7% of the tested H. pylori strains, and there was no significant association between babA2 genotype status and the severity of gastric disease. Therefore, babA2 gene cannot be considered as a sole marker for determining the infection outcomes.